2021
DOI: 10.1016/j.amsu.2021.102777
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of burnout syndrome and its association with adherence to safety and practice standards among anesthetists working in Ethiopia

Abstract: Background Burnout amongst healthcare professionals is a serious challenge affecting health care practice and quality of care. The ongoing pandemic has highlighted this on a global level. This study aimed to determine the prevalence of burnout syndrome and its association with adherence to safety and practice standards among non-physician anesthetists in Ethiopia. Methods A cross-sectional survey was conducted amongst non-physician anesthetists throughout Ethiopia in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This occurs by not following protocols, admitting or discharging patients prematurely to make the ED more manageable, not fully answering patients’ questions, and not treating patients’ pain in a timely manner. 53 , 62–67 Furthermore, higher levels of burnout were correlated with not communicating important information during handoff, not discussing treatment plans with important staff, and ordering more laboratory or radiology studies because of feelings of being busy. 53 , 62–67 One European study found that burnout among EPs was associated with self-reported mistakes that inadvertently could have harmed or did in fact harm patients.…”
Section: Effects Of Compassion Fatigue On Patients In the Emergency D...mentioning
confidence: 99%
See 2 more Smart Citations
“…This occurs by not following protocols, admitting or discharging patients prematurely to make the ED more manageable, not fully answering patients’ questions, and not treating patients’ pain in a timely manner. 53 , 62–67 Furthermore, higher levels of burnout were correlated with not communicating important information during handoff, not discussing treatment plans with important staff, and ordering more laboratory or radiology studies because of feelings of being busy. 53 , 62–67 One European study found that burnout among EPs was associated with self-reported mistakes that inadvertently could have harmed or did in fact harm patients.…”
Section: Effects Of Compassion Fatigue On Patients In the Emergency D...mentioning
confidence: 99%
“… 53 , 62–67 Furthermore, higher levels of burnout were correlated with not communicating important information during handoff, not discussing treatment plans with important staff, and ordering more laboratory or radiology studies because of feelings of being busy. 53 , 62–67 One European study found that burnout among EPs was associated with self-reported mistakes that inadvertently could have harmed or did in fact harm patients. 68 EPs with CF communicate less thoroughly and less well, and are more likely to have unchecked cognitive biases that impact patient care.…”
Section: Effects Of Compassion Fatigue On Patients In the Emergency D...mentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was adopted and validated with some of the questions based on a framework similar to that of previous studies on infectious disease outbreaks [10,11,12].…”
Section: Study Instrumentsmentioning
confidence: 99%
“…Burnout generally affects the mental health of the health workforce, job satisfaction and minimizes patient"s quality of care. During the COVID-19, response health professionals were affected by burnout, with consequent decrease in work performance and patient care which could have negative impact on the family and society [9,10] The burnout rate increased among the HCWs during the COVID-19 pandemic, but there is virtually no published data on burnout among health workforce in Ethiopia at the national level. Thus, this assessment was conducted to examine the prevalence of burnout among the health workforce during the COVID-19 response in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%